ALTERNATIVE HABITAT FOR THE ANDEAN LAPWING (VANELLUS RESPLENDENS) AND NOTES ABOUT ITS FEEDING BEHAVIOUR DURING WINTER IN FARMLANDS IN THE CITY OF PAUZA (AYACUCHO SUR), PERU - Ortiz, Enver (2015)
Observations are reported of presence of Andean lapwing (Vanellus resplendens) flocks during the winter season from 2009 to date in farmlands of Pauza city in south of Ayacucho, Peru.